Estrategia de potencialización de agencias intermediarias para el crecimiento en ventas y penetración del mercado PYME en el suroccidente colombiano por parte de la empresa CESCE Colombia (Segurexpo) (2024)
Currently, the market and its high competitiveness require companies to reinvent not only their internal processes but also their sales strategies, which are a large part of their face to the outside world. An excellent product or an excellent brand does not guarantee a successful result, it is also necessary to properly exploit all available resources and channels, in which the expected reach can be achieved and improve the accuracy of the planning. Intermediation has been a historical and efficient tool in cases where it has been used by large companies seeking to reach audiences where they could not or would not be able to. The choice of the right distribution channel is crucial for the success of a product - Philip Kotler, Marketing Management - . This reinforces the importance of distribution channels, which are a path to be developed to reach not only customers, but also the success of a corporate strategy. Not only are sales strategies and distribution channels important, but also the chosen segment is highly relevant, so that all efforts are correctly directed and penetrate to the level needed and in the potential population. In this case, the segment will play a significant role, as it has not been previously exploited nor with the approaches that will be proposed. We will begin this journey with context and market information that will allow us to approach the tactics to niches where there is enormous potential and a minimal risk of failure.